What if there were not secondary schools in city neighborhoods? Tensions between the improvement of schooling conditions and the defunding of some socio-educational inclusion policies in the Province of Córdoba - Maria Cecilia Bocchio (Arizona State University, 2019)
This article presents a case study in a secondary school located in a City - Neighborhood of Córdoba Capital whose students are, predominantly, the first generation of families to access, stay, and graduate from secondary school. From the contributions of Social Regulation Theory (Reynaud, 1997, 2003), this study accounts for the dynamics that cut across the policies associated with the expansion of compulsory secondary schooling (ESS) when they reach the school and translate into growth of school enrollment and struggles to improve the conditions of the students' schooling. Given the recent loss of funding of some policies aimed at guaranteeing ESS, we hypothesize that in the selected school the tension between control of outcomes accountability for results and school autonomy would be deepening the process of delegating responsibility on the school over the schooling of vulnerable sectors.